2012
DOI: 10.1039/c2cp43275g
|View full text |Cite
|
Sign up to set email alerts
|

On the intrinsic photophysics of indigo: a time-resolved photoelectron spectroscopy study of the indigo carmine dianion

Abstract: The intrinsic photophysics of indigo has been studied using gas-phase time-resolved photoelectron imaging of the indigo carmine dianion (InC 2À ). The action spectrum reveals that the gas-phase absorption spectrum arising from the S 1 ' S 0 transition in InC 2À has a similar solvent shift to that of neutral indigo. Femtosecond spectroscopy shows that the S 1 state decays on a 1.4 ps timescale. Through isotopic substitution, the primary mechanism on the S 1 excited state can be assigned to an intra-molecular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…We had previously also measured an action spectrum of InC 2-by monitoring only the electron loss channel and this indicated a 90 broad absorption with a maximum at 2.2 eV (560 nm). 28 An overview of the energy level diagram of InC 2-is shown in Fig. 3 and this compares well with previous DFT calculations computed with the Gaussian09 package 38 and using the B3LYP functional 39 with a 6-311++G** basis set.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…We had previously also measured an action spectrum of InC 2-by monitoring only the electron loss channel and this indicated a 90 broad absorption with a maximum at 2.2 eV (560 nm). 28 An overview of the energy level diagram of InC 2-is shown in Fig. 3 and this compares well with previous DFT calculations computed with the Gaussian09 package 38 and using the B3LYP functional 39 with a 6-311++G** basis set.…”
Section: Resultssupporting
confidence: 80%
“…In our previous study on InC 2-, we showed that the S 1 state is short lived, with a lifetime of 1.2 ps. 28 Hence, the S 1 lifetime is an 15 order of magnitude longer than our femtosecond pulses, but at least 3 orders of magnitude shorter than the nanosecond pulses. The consequence of this is that multiple photons can be absorbed using the same S 1 ← S 0 transition, leading to large amounts of energy into the internal modes of InC 2-(2.30 eV per photon 20 cycle).…”
Section: Effect Of Pulse Duration On Pe Anisotropy: Nanosecond Vs Fementioning
confidence: 68%
See 2 more Smart Citations
“…Our choice of ESI was primarily driven by our desire to study large complexes that could be probed by time-resolved PE imaging, 57-60 including dianions. [61][62][63][64] The focus here is on radical anions and actually, ESI is not the most ideal source as it tends to deprotonate molecules and form closed-shell anions. Nevertheless, the versatility of ESI is very appealing and, with care, radical anions can be readily generated in many cases.…”
Section: Experimental Considerationsmentioning
confidence: 99%